Implementation of Public Policy in Efforts to Achieve Social Justice for the Community - Herabudin Herabudin (Budapest International Research and Critics University, 2022)
One of the state's most important priorities is to ensure its citizens' health and happiness. For this goal to be accomplished, it is necessary to put into place several different mechanisms, all of which should be reflected in the public policies that are ultimately adopted. The many obstacles that must be overcome to acquire riches through the implementation of public policy constitute a task in their own right. The topic of investigation for this line of inquiry will be how the application of public policies might reduce or do away with the illness that affects the well-being of individuals and bring about equality in the current world. Most people don't think of equality in terms of financial parity; rather, they focus on having equal access to opportunities to achieve it. It is necessary to connect to the idea of social justice while tackling the problem of inequality. In this essay, I will first review and critique the present literature on poverty, inequality, and social justice. Then I will propose a variety of unique techniques for eradicating inequality. Although political activities are necessary to achieve these goals, Ultimately, it is the responsibility of the public administrator to establish detailed plans or procedures for carrying them out. In this essay, we will investigate how public officials might work to advance equality and social justice.